Pengembangan Lembar Kerja Peserta Didik Berbasis Jigsaw Dengan Tema Benda-benda di sekitar kita Kelas V Sekolah Dasar : lkpd berbasis jigsaw - Des Sinta Sari; Vika Nadiana; Eka Nurkomsiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This Research and Development aims to develop LKPD teaching materials and to know the effectiveness of LKPD based Jigsaw. This research method is a research and development by Borg & Gall. The population in this study were students in Elementary School Margototo Kecamatan Metro Kibang as many as 145 students and 4th grade research sample Elementary School 1 Margototo as many as 40 students. Instruments used are tests and non-tests to measure learners' learning outcomes in terms of cognitive aspects. The final product of this research is LKPD which has been validated by material experts, media experts and classroom teachers. The results showed that LKPD was developed based on the needs analysis of learners and can be used in the National Curriculum, LKPD interesting and easy to use seen from the student's response, and LKPD effective for improving learners' learning outcomes before using and after using LKPD.